Piezoelectric actuators for acoustic mixing in microfluidic devices: numerical prediction and experimental validation of heat and mass transport - Catarino, Susana Oliveira (2014)
Microfluidic devices have been used for handling and analyzing micro scale fluidic quantities with smallconcentrations, relying on smaller devices, with increased portability and availability. This paper pro-poses a solution to reduce the mixing time required in microfluidic devices analyses, without the needof pumps or moving parts. To speed up the required mixing, acoustic streaming is proposed. Two dif-ferent piezoelectric materials, PZT and -PVDF, are explored, concerning their actuation frequencies, forintegration in microfluidic devices. Their layout, actuation frequency and behavior were compared formixing two fluids inside a microfluidic reaction chamber. Numerical simulations and experimental testsshowed flow vortices generation and a significant mixing time reduction for both materials: above 90%for PZT and above 80% for -PVDF. It was also observed an increase of the temperature on the trans-ducers surface, which is advantageous for applications in which heating is necessary. The results showedagreement between simulations and experimental tests which can be useful for predicting new materialsbehavior for improving microfluidic devices mixing.